Natural cover permanence in two connectivity proposals between protected wildlife areas of Costa Rica (UNED Research Journal, 2019)
Introduction: Riparian zones are an alternative for connectivity in landscapes where natural cover has been fragmented. Objective: To analyze structural connectivity between two protected wildlife areas of Costa Rica, through riparian zones, and an officially established route. Methods: The two protected wildlife areas were Lomas Barbudal Biological Reserve and Miravalles Protective Zone, Guanacaste province. Using supervised classification of Landsat images from years 1997 and 2017, land cover was obtained for riparian zones and the official route. Based on this information, forest permanence was analyzed and several fragmentation indicators calculated for the two connectivity proposals. Results: Forest was more extensive and permanent in the riparian zones; nevertheless, both connectivity proposals had interruptions in connectivity and isolated forest sectors. In the official route, interruption was caused mainly by urban areas; riparian zones were interrupted by agriculture. Conclusion: Riparian zones would also provide good structural connectivity, but they need to recover such connectivity too.
Keywords: structural connectivity; dispersal routes; protected wildlife areas; natural cover permanence; riparian zones.